2012
DOI: 10.1007/s10897-012-9557-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Counselors’ Current Use of Personal Health Records‐Based Family Histories in Genetic Clinics and Considerations for Their Future Adoption

Abstract: Given the widespread adoption of electronic medical records and recent emergence of electronic family history tools, we examined genetic counselors’ perspectives on the emerging technology of the personal health record (PHR)-based family history tool that links to an electronic medical record (EMR). Two-hundred thirty-three genetic counselors responded to an on-line survey eliciting current use of electronic family history (EFH) tools and familiarity with PHR-based family history tools. Additionally, after bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…electronic medical records to a family history tool would be time saving (Widmer et al 2013). This has been supported by other studies concluding that time and effort could be saved by enabling counsellees to record their family history by electronic methods (Guttmacher et al 2004, Hulse et al 2011.…”
Section: Introductionmentioning
confidence: 91%
“…electronic medical records to a family history tool would be time saving (Widmer et al 2013). This has been supported by other studies concluding that time and effort could be saved by enabling counsellees to record their family history by electronic methods (Guttmacher et al 2004, Hulse et al 2011.…”
Section: Introductionmentioning
confidence: 91%
“…Widmer et al (2013) found that only 16% of the genetic counselors they surveyed had ever had access to an electronic version of their patients’ family histories, and a smaller percentage had patient populations who consistently had access. Barriers to use include concern over ease of use and the inability to modify family history with additional information collected during the session (Widmer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Widmer et al (2013) found that only 16% of the genetic counselors they surveyed had ever had access to an electronic version of their patients’ family histories, and a smaller percentage had patient populations who consistently had access. Barriers to use include concern over ease of use and the inability to modify family history with additional information collected during the session (Widmer et al, 2013). Also, many family history collection tools do not allow both patient and provider to input and modify family history information within the electronic system, or collect medical history, which is an important component of the cancer risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used tools by genetic counselors, My Family Health Portrait (MFHP; freely available at www.familyhistory.hhs.gov ) and Family Healthware ( http://www.cdc.gov/genomics/about/family.htm ), are not integrated into EHR systems ( Feero, Bigley and Brinner, 2008 ). Qualitative work by Widmer et al among genetic counselors found limited adoption of these tools because of their lack of integration into EHR systems ( Widmer et al, 2013 ), seeking tools that were consistent (i.e., standardized), reduce repetitive questions, and improve clarity of clinical implications.…”
Section: Discussionmentioning
confidence: 99%